2008
DOI: 10.3174/ajnr.a1044
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility, Interrater Agreement, and Age-Related Changes of Fractional Anisotropy Measures at 3T in Healthy Subjects: Effect of the Applied b-Value

Abstract: BACKGROUND AND PURPOSE:There is no reproducibility study of fractional anisotropy (FA) measurements at 3T using regions of interest (ROIs). Our purpose was to establish the extent and statistical significance of the interrater variability, the variability observed with 2 different b-values, and in 2 separate scanning sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 28 publications
12
44
3
Order By: Relevance
“…There are a few studies reporting ADC 20,47 and FA values in the normal population. 20, 48 The values we found for FA are generally lower than the reference values for the normal population according to Brander et al 20 FA values in the subcortical cerebellum are reported to be higher in normal subjects, as compared with our patients. 39 Also, ADC at the posterior limb of internal capsule and subcortical cerebellum are considerably higher in our population compared with those found by Helenius et al 47 There might be a modification of DTI parameters (reduction of FA and increase in ADC) in patients with acute SAH that has to be confirmed in further studies.…”
Section: August 2017contrasting
confidence: 36%
“…There are a few studies reporting ADC 20,47 and FA values in the normal population. 20, 48 The values we found for FA are generally lower than the reference values for the normal population according to Brander et al 20 FA values in the subcortical cerebellum are reported to be higher in normal subjects, as compared with our patients. 39 Also, ADC at the posterior limb of internal capsule and subcortical cerebellum are considerably higher in our population compared with those found by Helenius et al 47 There might be a modification of DTI parameters (reduction of FA and increase in ADC) in patients with acute SAH that has to be confirmed in further studies.…”
Section: August 2017contrasting
confidence: 36%
“…Jansen and colleagues performed two scans on 10 healthy subjects, noting median lobar DTI(FA) values for ICC of 0.75–0.86 (Jansen, Kooi, Kessels, Nicolay, & Backes, 2007). Bisdas and colleagues performed two scans separated by 2 weeks on 12 subjects, noting low individual FA tract MCV (0.4%–10%) (Bisdas, Bohning, Besenski, Nicholas, & Rumboldt, 2008). Vollmar and colleagues noted FA MCV of 0.8%–3.0% and ICC of 0.82–0.99 in nine subjects, with the whole‐brain average FA showing the smallest MCV (Vollmar et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been illustrated that the imaging processing pipeline is important for reproducibility (Vollmar, O'Muircheartaigh et al 2010). The differences in DTI due to different numbers of diffusion gradients and acquisition parameters are small relative to the variability of FA measures between sessions, which is in accordance with previous systematic evaluation of the reproducibility of FA (Bisdas, Bohning et al 2008, Vollmar, O'Muircheartaigh et al 2010. Whole brain analysis has good reproducibility but cannot be sensitive to pathological changes in clinical studies because it is hard to estimate the pathological state of the tissue (Jansen, Kooi et al 2007, Assaf andPasternak 2008).…”
Section: Serial Mri Studiessupporting
confidence: 89%